2007
DOI: 10.1016/j.rmed.2007.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of community-acquired pneumonia in patients with chronic obstructive pulmonary disease

Abstract: Community-acquired pneumonia in patients with COPD was associated with epidemiological and clinical particularities mainly related to the underlying disease but showed only minor differences in outcome parameters. Gram-negative bacilli and P. aeruginosa are potential pathogens that need to be considered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
34
1
5

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 23 publications
3
34
1
5
Order By: Relevance
“…This approach is in contrast to that of Pifarre et al [9], who studied pneumonia patients to gain insight into the characteristics of CAP in patients with COPD. To date, little data is available on the management and course of COPD patients with exacerbations who present acutely with or without pneumonia.…”
Section: Discussionmentioning
confidence: 98%
“…This approach is in contrast to that of Pifarre et al [9], who studied pneumonia patients to gain insight into the characteristics of CAP in patients with COPD. To date, little data is available on the management and course of COPD patients with exacerbations who present acutely with or without pneumonia.…”
Section: Discussionmentioning
confidence: 98%
“…We failed to request missing data of interest by contacting the corresponding author of the original study. 23 The reviewers cross-checked all extracted data. Discrepancy between reviewers was resolved by discussion until consensus was reached.…”
Section: Data Extractionmentioning
confidence: 99%
“…All cohort studies ascertained the diagnosis of CAP based on chest radiographic findings, whereas the two case-control studies identified the cases of CAP according to the International Classification of Diseases (ICD-10) codes. Eight cohort studies confirmed the presence of COPD by spirometric criteria, 15,[18][19][20]23,[26][27][28] whereas the case-control studies 16,29 and one cohort study 17 identified COPD patients through medical records. The main characteristics of the included studies are summarized in Table 1.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar types of findings were also reported from Indian studies. 13 Identification and determining the clinical patterns and risk factors of Pneumonia (CAP) helps in adoption of regionally optimised diagnostic and therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%